Dialog Lintas Agama dalam Tafsir Mafatih Al-Gaib Karya Fakhr Ad-Din Ar-Raziy - Muhammad Syahran; Muhammad Zakir Husain; Ashabul Kahfi Dainur (SUHUF, 2026)
This study examines the assumption that Mafatih al-Gaib by ar-Raziy contains a moderate and applicable form of interreligious dialogue that can strengthen religious moderation in Indonesia. Using a qualitative, library-based approach, the research focuses on Christians (Nasrani) as the primary subject, analyzing Qur’anic verses related to social issues within the Indonesian context. A synchronic–diachronic semiotic recontextualization method is employed and linked to the religious moderation framework of the Indonesian Ministry of Religious Affairs. The findings demonstrate moderate narratives in ar-Raziy’s dialogical exegesis, including the permissibility of non-Muslims entering mosques, exchanging greetings with them, and appointing non-Muslim leaders. These interpretations reflect a dialogical pattern incorporating pro, contra, and moderate arguments. Substantively, the findings align with key pillars of religious moderation, such as national commitment, tolerance, cultural accommodation, and non-violence. The study contributes to strengthening religious moderation curricula and provides relevant material for educational and religious outreach programs.